Sensory evaluation of principal pear cultivars from North Patagonia, Argentina - Calvo, Paula Cecilia; Gittins Lopez, Cecilia Gabriela; Miranda, María José; Barda, Nora Beatriz (ISHS, 2025)
Trabajo presentado al XI International Pear Symposium, Argentina, 2010